2016
DOI: 10.1371/journal.pone.0153313
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Economic Disparities in Use of Family Planning Methods among Pakistani Women: Findings from Pakistan Demographic and Health Surveys

Abstract: BackgroundSeveral developing countries like Pakistan step into Sustainable Development Goals period with crucial maternal and child health needs that need to be addressed for improving health outcomes among people. We aim to explore existent socio-economic disparities in use of family planning methods (FPM) among Pakistani women, and compare any such inequalities between the years 2006 and 2013.SettingPakistan Demographic and Health Surveys (PDHS) 2006–7 (n = 9177) and the most recent 2012–13(n = 13558) data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
15
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
6
15
1
Order By: Relevance
“…This is not surprising since wealth is correlated with education which facilitates the increase to use (Ortayli & Malarcher, 2010). This nding supports previous studies that showed that higher socioeconomic status improves the use of family planning services (Aslam et Al., 2016). Studies show that economically self-su cient women are more likely to utilize contraception as it enhances their ability to make rational decisions on reproductive health issues (Ortayli, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is not surprising since wealth is correlated with education which facilitates the increase to use (Ortayli & Malarcher, 2010). This nding supports previous studies that showed that higher socioeconomic status improves the use of family planning services (Aslam et Al., 2016). Studies show that economically self-su cient women are more likely to utilize contraception as it enhances their ability to make rational decisions on reproductive health issues (Ortayli, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The argument is that, the rural poor have less income compared to their urban counterparts leading to the parallel disparities that exists between them in family planning utilization. This nding supports the ndings of a previous study that showed that socio-economic gap or differences in family planning utilization exists and had persisted among women and this had disadvantaged the poor (Aslam et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…9 A study in Pakistan concluded that, despite a growing family planning program over time, a gap remained in use of family planning by socioeconomic factors linked to the poor and illiterate groups. 10 A study in West Bengal, India, revealed a positive association between the level of media exposure and the use of modern contraceptive methods among all age cohorts. 11 Furthermore, a study conducted in Benin Republic found that women's education, discussion about family planning, number of living children, fertility preference, marital status, household wealth index, sex of household head, religious membership, and place of residence were significant covariates of modern contraceptive use.…”
Section: Conclusion Onclusionsmentioning
confidence: 99%